Effect of polymer loading on anti-swelling efficiency and formaldehyde emission of sesenduk wood impregnated with low molecular weight phenol formaldehyde (LMWPF) and urea admixture - Chua, Arleen Huei Wen (2018)
A study was undertaken to determine the effect of polymer loading on dimensional stability and formaldehyde emission of sesenduk (Endospremum diadenum) wood treated with low molecular weight phenolic resin and urea admxiture. A total of 32 pieces air-dry wood strips were prepared in a dimension of 165 mm long x 50 mm wide x 5 mm thick. The cut wood strips were assorted according to density before treatments to ensure that each of the treatment group had the equal number of the same density to avoid variation. The wood with initial moisture content of 14 % were impregnated with LmwPF (20 % and 30%) weight by volume and admixture of LmwPF + 0-15 % urea based on solid PF by using vacuum-pressure cylinder. Initial vacuum was applied to the cylinder for 15 minutes followed by soaking under the pressure for 30 minutes. After that, the wood strips were partially cured at 70 °C for three hours and cured at 150 °C for one hours. Finally, the impregnated wood were conditioned at 25 °C±2, 65 ±2 % humidity and 12 % EMC. The results showed that the treatments increased the physical properties of the sesenduk such as WPG, density and ASE. The impreg sesenduk that had been treated with urea admixture had lower FE than those treated with LmwPF alone. Urea as a formaldehyde scavenger can reduce the formaldehyde emission and achieved E1 standard in EN120. This study also found that anti-swelling efficiency (ASE) of the treated sesenduk was highly correlated to the polymer loading. The higher the polymer loading, the higher the dimensional stability achieved by the treated sesenduk.